UMPSA will collaborate with Beifang International Education Group on TVET development - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 17 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) will collaborate with Beifang International Education Group (Beifang) in the development of higher education, especially in the field of Technical and Vocational Education and Training (TVET) which will utilise expertise sharing related to electric vehicles (EV), artificial intelligence (AI), internet of things (IoT), solar and information technology.